Chaebol-affiliated analysts: Conflicts of interest and market responses - Song, Kyojik “Roy”; Mantecon, Tomas; Altintig, Z. Ayca (Journal of Banking & Finance, 2012)
Some Korean business groups, or chaebols, have a large stake in securities firms that issue analysts’ reports on their member companies. This structure is unique in that industrial companies and securities firms are affiliated and operate within the same group. We investigate the informational content of earnings forecasts, stock recommendations and target prices made by the chaebol-affiliated analysts, using data collected between 2000 and 2008. The chaebol analysts tend to make more optimistic earnings forecasts for the member companies. The mean EPS forecast error (5.36%) of the affiliated analysts for the same chaebol company are significantly larger than that (3.23%) of other chaebol and independent analysts. The chaebol analysts also assign better recommendations by almost one level and set target prices 2.5% higher to the member companies after controlling for company and analyst characteristics. These results are consistent with the hypothesis that chaebol analysts’ reports are biased by conflicts of interest. Stock market reactions do not differ in response to announcements of stock recommendations issued by affiliated vs. non-affiliated analysts. This suggests that capital markets do not recognize the conflicts of interest inherent in chaebol analysts’ reports.